2020
DOI: 10.1002/npr2.12150
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nesting behavior, selective increases in locomotor activity in a novel environment, and paradoxically increased open arm exploration in Neurogranin knockout mice

Abstract: Aims Neurogranin (NRGN) is a postsynaptic protein kinase substrate that binds calmodulin in the absence of calcium. Recent studies suggest that NRGN is involved in neuropsychiatric disorders, including schizophrenia, ADHD, and Alzheimer's disease. Previous behavioral studies of Nrgn knockout (Nrgn KO) mice identified hyperactivity, deficits in spatial learning, impaired sociability, and decreased prepulse inhibition, which suggest that these mice recapitulate some symptoms of neuropsychiatric disorders. To fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
2
9
1
Order By: Relevance
“…However, other studies with the 6-OHDA lesion mice model of ADHD show increased sensitivity to mechanical and thermal stimuli [72]. Also, the Neurogranin knockout mice show hyperactivity and elevated pain sensitivity, together with behaviour traits associated with several human disorders [73]. In our study, control females showed a higher threshold to pain than males.…”
Section: Discussioncontrasting
confidence: 43%
“…However, other studies with the 6-OHDA lesion mice model of ADHD show increased sensitivity to mechanical and thermal stimuli [72]. Also, the Neurogranin knockout mice show hyperactivity and elevated pain sensitivity, together with behaviour traits associated with several human disorders [73]. In our study, control females showed a higher threshold to pain than males.…”
Section: Discussioncontrasting
confidence: 43%
“…The reductions in cage ambulation observed in the Ng+/- mice compared to WT mice requires further investigation. While this is consistent with previous work in our lab with these mice ( 27 ), others have shown that Ng knockout mice exhibit traits of hyperactivity ( 43 , 44 ). However, hyperactivity was only observed in an open field test, and not in a familiar environment such as their home cage ( 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…This module also included Ntsr1 , the gene that encodes the principal receptor for the anorexigenic peptide neurotensin 23 . Genes with decreased expression in obese Nnat +/-p versus Nnat +/+ mice included neurogranin, a thyroid-regulated gene whose loss has been reported to result in an anxiety-like phenotype 24 (Supplementary Table 1 B). However, module analysis of female PVN did not show a substantial overlap in constituent genes between modules identified from male and female mice (Supplementary Table 1 A).…”
Section: Resultsmentioning
confidence: 99%